Nilai Pendidikan dalam Pemikiran Ali Bin Abi Thalib - Meliantina Meliantina (LPPM Politeknik Pratama, 2024)
This study aims to contribute directly in modern-day character education that is growing over time with the sudden need to be refined. This research uses descriptive qualitative research, and the type of study is a library / research library that collects data or scientific papers aimed at the object of research or data collection is the library. The study is carried out to solve a problem that basically relies on a critical and in-depth study of the materials relevant book. In this study, researchers found Ali ibn Abi Talib thinking about characters such as education, honesty, simplicity, hard work, tolerance, patience, respect, and passion. Based on the research results can be concluded: Thought Ali bin Abi Talib exist in the form of a book Nahj al-Balagha words. Sermons. Speeches and letters are the values ​​of character education with a special feature that is religious and universal, relevant, and the significance of which can add and support character education to the modern world as it is today.